2020
DOI: 10.3390/su13010249
|View full text |Cite
|
Sign up to set email alerts
|

BIM-Enabled Virtual Reality (VR) for Sustainability Life Cycle and Cost Assessment

Abstract: Virtual Reality (VR) is receiving ever-increasing attention and is utilized by many construction companies in their current practices. This paper aims at a critical investigation of the impact of VR technology on how sustainability and cost are understood and perceived by the users in building design projects, which could lead to improving and supporting the actual building design processes. The research study focused on evaluating design alternatives using Building Information Modeling (BIM)-enabled VR techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
(39 reference statements)
0
22
0
Order By: Relevance
“…Despite the emerging global campaign for sustainable development, the construction industry is still prevalently highlighted as critical in terms of its sustainability impact [51,52]. With the emerging design and studies on improving sustainable development through BIM-based life cycle sustainability assessment for buildings, the adoption and interest are still at a low phase [53,54].…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Despite the emerging global campaign for sustainable development, the construction industry is still prevalently highlighted as critical in terms of its sustainability impact [51,52]. With the emerging design and studies on improving sustainable development through BIM-based life cycle sustainability assessment for buildings, the adoption and interest are still at a low phase [53,54].…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Enscape is a plugin for Revit and Rhino that provides a VR viewer for walkthrough explorations of designs, with changes made in Revit being instantaneously displayed in VR (Enscape,2019). Enscape has been used in several published case studies such as an examination of the bill of quantities in a furnished house (Davidson et al, 2020) and a lifecycle cost assessment of building facades (Kamari et al, 2021). Mindesk plugin for Rhinoceros exposes Rhino modelling functionality to VR, allowing a user to use controllers and a VR version of its user interface to create designs in an immersive mode, and including an option to use Grasshopper for parametric modeling (Mindesk,2019b).…”
Section: Bim and Parametric Structural Design In Vrmentioning
confidence: 99%
“…Relevant mainland scholars [25] analyzed the relevant technologies of digital landscape architecture from the aspects of acquisition, storage and sharing of relevant data by constructing the overall digital framework of landscape architecture, and expounded the advantages of digital landscape architecture system from the aspects of monitoring system, security system, and data management system. Relevant European and American industrial companies [26,27] decomposed the digital design of landscape architecture, and concluded that the digital landscape design mainly includes several important modules, such as generalized intelligent sensor network technology, landscape data transmission, landscape spatial data processing and analysis, landscape spatial data management, landscape spatial data mining and analysis, and believed that the information technology, Internet of things technology, grid computing Artificial intelligence technology, and pattern recognition technology can complete the whole process of digital design of landscape architecture. In the specific application of digital design technology of landscape architecture, relevant scholars [28] used BIM Technology to apply BIM Technology to the planning, design, analysis, and evaluation of digital design, so as to improve the design efficiency, deepen the designer's understanding of landscape design, and improve the design quality.…”
Section: Related Research: Analysis On the Research Status Of Intelli...mentioning
confidence: 99%